2023
DOI: 10.3390/w15061077
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Groundwater Table Inclination for Nature-Based Replenishment of Groundwater-Dependent Ecosystems by Managed Aquifer Recharge

Abstract: Managed aquifer recharge (MAR) is an increasingly popular technique; however, the significance of groundwater flow dynamics is rarely examined in detail regarding MAR systems. In general, a high hydraulic gradient is not favoured for MAR implementation, as it causes higher water loss and mixing of recharge water with native groundwater. However, during groundwater-dependent ecosystem (GDE) rehabilitation, these hydraulic gradient-driven flow processes can be taken advantage of. The aim of this research is to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…As a solution, in the settlements, rainwater or surface runoff could be collected and infiltrated as well as the treated wastewater. These solutions could effectively increase water levels on a catchment scale, too [7,31]. This way, not only in the regional recharge but also in the discharge position the water table could be elevated or at least maintained.…”
Section: Potential Solutions To Mitigate Water Affecting the Areas An...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a solution, in the settlements, rainwater or surface runoff could be collected and infiltrated as well as the treated wastewater. These solutions could effectively increase water levels on a catchment scale, too [7,31]. This way, not only in the regional recharge but also in the discharge position the water table could be elevated or at least maintained.…”
Section: Potential Solutions To Mitigate Water Affecting the Areas An...mentioning
confidence: 99%
“…In a successful MAR implementation, understanding groundwater flow conditions is crucial in order to determine the potential pathways of the retained, infiltrated, or injected water. This natural groundwater movement may also be useful for the rehabilitation of GDEs and wetlands by applying appropriate MAR solutions in the recharge areas of GDEs or wetlands [24,29,30], as a nature-based solution [31]. Szabó et al [31] found that the efficiency of this solution is dependent more on the position of the MAR solution in the flow systems rather than on the amount of retained water.…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrate how an existing GW model can be an effective screening tool for initial MAR for enhanced baseflow suitability. Some key benefits of using a regional GW model to evaluate the baseflow response over more conceptual approaches, such as analytical solutions (Knight et al, 2005) or simplified 2D models (Szabó et al, 2023) is that the numerical model is able to account for (1) anthropogenic effects (pumping, additional recharge from SW irrigation) that can alter the baseflow response, (2) geological heterogeneity that may control local hydraulic connection to rivers or boundaries, and (3) the effects of transient hydrologic conditions such as river stage, periodic well pumping, irrigation, and changing water table elevations that can alter the baseflow response (Kendy and Bredehoeft, 2006;Ferencz and Tidwell, 2022). This study benefitted from the regional model being designed in MODFLOW 6, which is compatible with FloPy.…”
Section: Benefits and Considerations Of Using An Existing Gw Modelmentioning
confidence: 99%
“…A number of studies have explored approaches to characterize site suitability for MAR ranging from regional (Smith and Pollock, 2012;O'Geen et al, 2015;Gibson et al, 2018) to local scales (Lee et al, 2019). The sophistication of approaches ranges from evaluating analytical solutions to characterize infiltration and groundwater mounding (Smith and Pollock, 2012), to simplified conceptual numerical models (Szabó et al, 2023), to three-dimensional (3D), transient regional groundwater simulations (Russo et al, 2015;Kourakos et al, 2019). The primary focus of MAR characterization is identifying surface and aquifer characteristics that favor high infiltration rates and large storage capacities (Smith and Pollock, 2012;Gibson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are many processes related to the functioning of NbS in relation to the propagation of floods and droughts on a landscape scale that are not well described or need additional attention during the planning, design and implementation phase of an NbS. For example, rainfall interception (and evaporation) for different types of vegetation and canopy structures (Muzylo et al, 2009), seasonality and pre-event effects (Fennell et al, 2023), the impact of climatic zone and local conditions (Burek et al, 2012), the role of soil carbon content (Fennell et al, 2022), and linkage between the unsaturated zone and the deeper ground water (Szabó et al, 2023) all play a role in defining the overall functioning of a NbS (Kumar et al, 2021a). In addition, the linkage with the impact of selected measures for floods and droughts on changes in water quality and biodiversity must be improved using easy-to-translate hydrological boundary condition indicators (e.g., minimum flow velocities for rheophilic fish communities and desired ground-water levels in summer seasons for groundwater dependent on vegetation communities).…”
Section: Improve Process Understandingmentioning
confidence: 99%